ANALISIS PERUBAHAN STRUKTUR EKONOMI (ECONOMIC LANDSCAPE) JAWA TENGAH (ANALISIS INPUT-OUTPUT PERIODE 2000-2013) - Fatmawati, Anisa; Iskandar, Deden Dinar (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
This research aims to find changes of economic structure in Central Java from 2000 to 2013. This reasearch uses input-output analysis which widely used to analyze the interrelationship on the economic sector, leading sector and economic multiplier sector. The Changes in the economic which analysed by using multiplier product matrix (MPM) illustrate the landscape of an economy. The results of this reasearch shows that sector with the highest number of multipliers output are the food industry, the other industrial sectors, the building sector, the restaurant and hotel sector and electricity sector. Then the sector that have highest number of multiplier income are the government sector, services sector, mining sector, livestock sector and building sector.Meanwhile the MPM analysis shows that there has been a change in the economic structure of Central Java during the period 2000 to 2013.